Disney+ : pricing and strategy - Robson, Karen (London : SAGE Publications: SAGE Business Cases Originals, 2022)
Disney is one of the leading entertainment companies in the world. Towards the end of 2019, it launched a streaming service called Disney+. The service has proven enormously popular: less than one year after its launch, Disney+ has already achieved its five-year goal with respect to registered users. In 2020, Disney added a premium tier to its streaming service called Premier Access, which users could purchase to get early access to Disney's premium content: the live action remake of Mulan (initially intended for theatrical release). This case provides an opportunity for students to understand and assess how the marketing environment impacts strategic decision-making in marketing. In addition, this case provides information on the pricing strategy implemented by Disney, which students can use to better understand strategies available when pricing new offerings.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Disney -- Case studies; Disney Enterprises (1996-) -- Case studies; Pricing -- Case studies; Streaming technology (Telecommunications) -- Prices -- Case studies